Guion Turístico en el Malecón de Babahoyo - Herrera Meza, Francisco Primitivo (2023)
The present case study refers to the implementation of a tourist script in the new Babahoyo boardwalk, where the problem raised refers to the limited availability of information about the tourist script for said boardwalk. Therefore, the present case study aims to identify the relevant and necessary information for the development of a tourist script about the boardwalk of the city of Babahoyo. In addition, it was framed under the research line “Development of tourism goods, products, services and processes”, and the research sub-line “Projections for the improvement of the quality of tourism goods, products, services and processes”, given that The most relevant information will be identified for the development of a tourist script about the new boardwalk in the city of Babahoyo. Likewise, as a research methodology, a qualitative approach was used in order to obtain relevant information that allows reaching conclusions, and at the same time, the type of descriptive research and documentary review was used and finally a survey was carried out directed at the inhabitants of the canton. . and entrepreneurs who are located within the boardwalk, with the purpose of obtaining relevant information to reach valid conclusions and recommendations.